Breakfast Consumption Patterns among the Students at Ahfad University for Women - Mohammed, Somiya Gutbi Salim (Edelweiss Applied Science and Technology, 2020)
Background: The intake of breakfast fuels the body with essential nutrients needed for the optimal function and helping the brain to concentrate during the day. Skipping breakfast puts the body at risking of entering into a starvation mode, leading to compensate and overeat later in the day. This current study was conducted between July 2019 and March 2020 at Ahfad University for Women. The main objective: To assess breakfast consumption pattern among the female students of Health sciences, Department of Nutrition and Dietetics at Ahfad University for Women in Sudan. Methodology: An epidemiological, cross-sectional study was conducted at Ahfad University for Women. A total of 100 students were selected by a stratified multi stage sample technique. Data was collected by using close ended questionnaire and analyzed by using SPSS (version 21). Results: The results showed that 80% of the students skipped their breakfast. Reasons for skipping their breakfast included lack of time to eat breakfast (32%), lack of appetite (18%), financial constraints (16%), stress and family eating patterns (6%), with only 2% mentioned they were following dietary regimen. Statistically significant differences was found between the observed and expected distributions of the sample regarding difficulties facing the students when skipping their breakfast (P=0.000), more than half of the students (n=56) faced many difficulties when skipping their breakfast. These included feeling hungry, lack of attention and being less active during their practical class. Linear regression model revealed that when students’ pocket money increased, some types of their food consumed increased by 90%. Conclusion: The study concluded that the majority of the student skipped their breakfast and there was significant relationship between students’ pocket-money and types of food consumed in the breakfast meal. Recommendation: The study recommends development of nutrition education program on the importance of breakfast meal for the student’s health.